2022
DOI: 10.5797/jnet.cr.2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Internal Carotid Artery Occlusion Caused by En Bloc Distal Embolization of Carotid Free-Floating Thrombus Treated by Mechanical Thrombectomy

Abstract: We report a case of internal carotid artery (ICA) occlusion caused by en bloc distal embolization of carotid free-floating thrombus (FFT) treated by mechanical thrombectomy.Case presentation: A 57-year-old woman was brought to our hospital with dysarthria, right hemiparesis, and motor aphasia. MRI and MRA revealed acute infarction due to middle cerebral artery occlusion. Carotid ultrasonography demonstrated a pedunculated mobile plaque in the left ICA. We diagnosed embolic infarction due to the carotid FFT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Resolution of FFT without worsening neurological symptoms occurs in 86% of medically treated patients. 3) Nonetheless, recurrent thrombosis 11) or distal embolization of thrombi 12) has also been reported in these patients. In this case, distal embolization was highly likely because the thrombus was giant and had a large volume.…”
Section: Discussionmentioning
confidence: 80%
“…Resolution of FFT without worsening neurological symptoms occurs in 86% of medically treated patients. 3) Nonetheless, recurrent thrombosis 11) or distal embolization of thrombi 12) has also been reported in these patients. In this case, distal embolization was highly likely because the thrombus was giant and had a large volume.…”
Section: Discussionmentioning
confidence: 80%
“…However, a therapeutic strategy for acute stroke with carotid FFT has not yet been established. Distal embolization can occur during anticoagulation therapy [5]; additionally, surgery is considered unsafe due to invasive general anesthesia or distal thrombus [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to conventional treatments, endovascular thrombectomy for carotid FFT has been reported [2,4,5,[7][8][9][10][11][12][13][14]. However, when balloon protection is used for distal protection, complete interruption of the ICA flow is undesirable in patients without hemodynamic intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Successful thrombus retrieval using a stent retriever or aspiration catheter has been reported in cases involving FFT without moderate or severe stenotic lesions. [3,4,8,12] However, few reports have described a combination of mechanical thrombectomy and CAS in cases of carotid artery stenosis with FFT. Tomoyose et al reported a case of FFT attached to severe stenosis of the ICA origin, in which the thrombus was removed by an aspiration catheter after PTA against the stenotic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Successful thrombus retrieval using a stent retriever or aspiration catheter has been reported in cases involving FFT without moderate or severe stenotic lesions. [ 3 , 4 , 8 , 12 ] However, few reports have described a combination of mechanical thrombectomy and CAS in cases of carotid artery stenosis with FFT. Tomoyose et al .…”
Section: Discussionmentioning
confidence: 99%